1994
DOI: 10.1113/jphysiol.1994.sp020132
|View full text |Cite
|
Sign up to set email alerts
|

An obligatory role for nitric oxide in autonomic control of mammalian heart rate.

Abstract: Cholinergic modulation of heart rate in isolated spontaneously beating single cells from the rabbit sino‐atrial node was investigated by measuring transmembrane ionic currents using the nystatin‐perforated patch whole‐cell voltage‐clamp technique. Carbamylcholine (CCh), a stable analogue of acetylcholine (ACh), significantly inhibited L‐type calcium currents (Ica(L) which had been augmented by beta‐adrenergic stimulation. In addition, CCh activated a potassium outward current (IK(ACh)). Both effects were block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
133
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(140 citation statements)
references
References 20 publications
6
133
0
1
Order By: Relevance
“…The data presented here in eNOS null cardiac myocytes nevertheless support previous work using pharmacologic NOS inhibitors and͞or NO donors that implicate an important role for eNOS in mediating parasym- pathetic nervous system signaling in the heart (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These data also support the contention that the effects of endogenously generated NO within cardiac myocytes are mediated by activation of guanylyl cyclase.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The data presented here in eNOS null cardiac myocytes nevertheless support previous work using pharmacologic NOS inhibitors and͞or NO donors that implicate an important role for eNOS in mediating parasym- pathetic nervous system signaling in the heart (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These data also support the contention that the effects of endogenously generated NO within cardiac myocytes are mediated by activation of guanylyl cyclase.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, a number of studies have implicated an important role for nitric oxide (NO) generation in mediating some aspects of muscarinic cholinergic and adrenergic signaling, both in intact hearts and in isolated myocytes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). NO, whether released by pharmacologic NO donors or generated by activation of endogenous NO synthases (NOS), has been shown to suppress the activation of voltage-sensitive Ca 2ϩ current (I Ca-L ) by ␤-adrenergic agonists (7)(8)(9)(10)(11)(12). Conversely, inhibition of NO generation within cardiac myocytes, including specialized pacemaker and conduction system cells, has been shown to blunt the negative inotropic and chronotropic effects of parasympathetic nerve stimulation in the mammalian heart in situ when infused with a ␤-adrenergic agonist (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…NO is now recognized to be an important endogenous vasodilator as well as a mediator or modulator of the myocardial response to other agents (Brady, Warren, Poole-Wilson, Williams & Harding, 1993;Han, Shimoni & Giles, 1994;. Endogenous NO has been shown to reduce the cardiotoxic properties of ET_1 in isolated hearts and attenuate the elevation of intracellular Ca¥ transients in ventricular myocytes .…”
Section: Influence Of No Generationmentioning
confidence: 99%
“…In relation to heart rate, Han, Shimoni & Giles (1994) found that NO altered spontaneous beating rhythm in isolated cultured sino-atrial node cell preparations. However, direct extrapolation of such observations to the whole animal is difficult.…”
Section: Introductionmentioning
confidence: 99%